Meta Analysis: Relationship between Obesity and Dental Caries in Children - Sholikha Dela Aprilia; Vilia Ayu Kumalasari; Wimmy Safaati Utsani; Hakim Anasulfalah (Masters Program in Public Health, 2022)
Background: Caries is an oral disease that often affects children around the world. The oral disease is related to several etiological factors with indicators of nutritional status, such as obesity and malnutrition. Studies linking overweight/obesity and caries experience in children have proved contradictory so far, the results including positive association, no association and inverse association. Therefore, this study aims to estimate the relationship between obesity and caries in children based on the results of several previous studies.Subjects and Method: This was a systematic study and meta-analysis. The search for articles was carried out by considering the eligibility criteria determined using the PICO model. The study population was children aged 6-15 years old with an intervention in the form of obesity, normoweight comparison and caries outcome. This article was collected for 3 weeks. The keywords to search for articles were as follows: “obesity” OR “overweight” AND “dental caries” AND “children”. The articles included in this study are full text articles with a cross sectional research design from 2012 to 2022. Articles were collected using the PRISMA flow chart. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 articles contained in this study, including 3 articles from Brazil which is the continent of South America, 2 articles from Mexico which is the continent of North America, 1 article from Nigeria which is the African continent, 2 articles from China and 1 article from Arabia which is the continent of Asia. The results showed that obesity can reduce the incidence of dental caries in children by 0.82 times higher compared to children with normal weight (aOR = 0.82; 95% CI = 0.45 to 1.52; p = 0.540)Conclusion: Meta-analyses show that overweight and obese children have a lower risk of developing early childhood caries. Keywords: Obesity, Overweight, Caries Dental, Children Correspondence:Sholikha Dela Aprilia. Department of Nursing, Universitas Diponegoro. Jl. Prof. Sudarto No. 13, Tembalang, Semarang, Central Java, 50275. Email: ikadela23@gmail.com Mobile: 081390211993.